Effect of alkaline modifiers on the structural, optical and crystallization properties of niobium germanate glasses and glass-ceramics - Nascimento Guedes, Luis Felipe; Marcondes, Lia Mara [UNESP]; Evangelista, Renato Oliveira; Batista, Gislene; Mendoza, Valentina Gacha; Cassanjes, Fabia Castro; Poirier, Gael Yves (Elsevier B.V., 2020)
Alkali niobium germanate glasses were prepared by melt-quenching in the ternary systems 75GeO(2)-15Nb(2)O(5)-10M(2)O with M = Li, Na, K, Rb and Cs. Thermal properties of these glasses and related glass-ceramics are strongly dependent on the alkaline modifier. Structural investigations by Raman allowed to determine that the alkali radius has an influence on the number of non-bridging oxygens and consequently on the average glass network connectivity. Raman spectra of sodium, potassium and rubidium germanate glass-ceramics exhibited slight changes when compared to the pristine glass and the new Raman features can be attributed to a 3D NbO6 network similar to orthorhombic niobium oxide. Characterization of the heat-treated glasses allowed to determine the crystalline phases precipitated in the samples and it has been shown that a single perovskite bronze-like phase of general formula M2Nb5O21 can be obtained in Na, K, and Rb-containing glasses. Luminescent properties of Eu3+-doped glasses pointed out a non-regular tendency where sodium-based glass seems to be the inflexion point of luminescent data with higher asymmetry around Eu3+ ions and higher quantum efficiency. In transparent glass-ceramics, the Eu3+ luminescent properties are clearly modified in the Na- and K-based samples with lower symmetry and quantum efficiency after heat-treatment. Such optical behavior is attributed to Eu3+ migration in the perovskite crystalline phase with highly distorted Eu3+ sites and shorter Eu3+-Eu3+ distances.
Keywords: Glass; Glass-ceramic; Germanate; Niobium; Alkali